PENGARUH STORE ATMOSPHERE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK ES KRIM “MIXUE” CABANG DHARMAWANGSA DI KOTA SURABAYA PADA KALANGAN MILLENNIAL - Madalena Retno Anggraini; Ni Made Ida Pratiwi; Ute Chairuz M Nasution (AGROTERAP : Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2023)
In the city of Surabaya, there are currently many ice, food and beverage outlets that are favores by all circle one of them is ice cream with various types. Currently there is new ice cream outlet in Surabaya namely Mixue which is now being visited by millennials. The purpose of the research is to know and analyze the influence of store atmosphere and product quality on purchasing decisions by using a descriptive quantitative research method then distributed questionnaires to 80 respondents as a sample and analyzed using t-test, f- statictical and R2 – determination. From the test results it can be concluded that there is a significant and simultaneous influence on variable store atmosphere and product quality on purchasing decisions. There are recommendations that can be given to mixue outlets and further researchers, to add facilities in the outlet and maintain product quality what is also owned for researchers can make the latest research to develop marketing science.